PWE-190 Outcome of Investigations for Iron Deficiency Anaemia in Men under 50 Years. (4th June 2013) - Patani, O D; Bharathi, S; Khalid, S
Abstract : Introduction: Iron-deficiency anaemia (IDA) occurs in 2–5% of men and postmenopausal women in the developed world. IDA is commonly due to blood loss from lesions in the gastrointestinal (GI) tract and malabsorption, accounting for 4–13% of referrals to gastroenterologists. In men over the age of 50 years and postmenopausal women there is established data on the incidence of GI pathologies causing IDA but such data for men under 50 years of age is not as robust. We carried out a retrospective analysis of outcomes of investigations for IDA in men under the age of 50 years over a period of 10 years in our hospital serving about 325, 000 population. Methods: Through the audit and clinical code department all male patients between 17 and 50 years of age investigated for IDA from 2000–2010 were identified retrospectively. The criteria used for diagnosis of IDA included haemoglobin level below the lower limit of normal, low ferritin and corresponding abnormalities of red cell indices. Data on outcome of investigations for IDA was collected from patient case notes and endoscopy, radiology and pathology records. Results: 52 patients were identified over the study period. The median haemoglobin was 9.3g/dl. The median age of the patients was 44 years. 44/52 (85%) had investigations recorded. 18/52 (33%) had gastroscopy (OGD) only. 26/52 (48%) had both OGD and colonic investigations. 7/52 (13%) had further investigations following normal bi-directional endoscopy including bone marrow, small bowel barium studies, capsule endoscopy and abdominal ultrasound with none of these additional investigations yielding further diagnostic information. With regards to colonic investigations 21/26 (81%) had colonoscopy, 3/26 (11%) had barium enema plus flexible sigmoidoscopy and 2/26 (8%) had CT scan. The findings of OGD were normal investigation 25/44 (57%), oesophagitis 5/44 (12%), peptic ulcer disease (PUD) 4/44 (9%), hiatus hernia 4/44 (9%), oesophageal cancer 1/44 (2%) and coeliac disease 2/25 patients with duodenal biopsies at OGD. The findings of lower GI investigations were normal investigations 16/29 (55%), haemorrhoids 5/29 (17%), inflammatory bowel disease (IBD) 3/29 (10%), polyps 2/29 (7%), colorectal cancer 2/29 (7%) and diverticulosis 1/29 (4%). Conclusion: Significant findings including PUD, malignancy and IBD constituted 19.2%. Malignancy accounted for 5.8% and this was comparable with previously reported prevalence of GI malignancy in patients with IDA (6–13%). In addition a proportion of investigations also yielded other diagnosis including oesophagitis and coeliac disease. Therefore it will be justified to investigate men under 50 years with IDA similarly to those over 50 years and postmenopausal women as suggested in most international guidelines Disclosure of Interest: None Declared.